Education, conflict and social cohesion - Tawil, Sobhi; Harley, Alexandra; Braslavsky, Cecilia (Studies in comparative education (Paris, France), 2004)
"The studies presented in this volume examine the role of educational policy change in social and civic reconstrution and the redefinition of national citizenship within the context of identity-based conflicts. The underlying assumption is that if educational change is to be a meaningful contribution to processes of national reconciliation and peace building in the context of civil strife, the complex linkages between schooling and conflict need to be explicitly recognised and explored."--Pref.